Utilizing genome wide data to highlight the social behavioral pathways to health: The case of obesity and cardiovascular health among older adults. (March 2021) - Davidson, Trent; Vinneau-Palarino, Justin; Goode, Joshua A.; Boardman, Jason D.
Abstract: We use genome-wide data from the 1992–2016 Health and Retirement Study (n = 12, 090) to characterize obesity among older adults as genetically or socially oriented. To illustrate the significance of this approach for social epidemiological research, we deem those with the lowest genetic risk for obesity to be socially-behaviorally obese and obesity among those with the highest polygenic risk is characterized as genetically oriented. We then examine the association between obesity and four indicators of cardiovascular health (type-2 diabetes, hypertension, heart problems, and stroke) among those with low, average, and high genetic risk. Our results show that the association between obesity and cardiovascular health is significantly higher for those with the lowest genetic risk (e.g., social-behavioral obesity). We also demonstrate important sex differences such that this association is particularly strong for heart problems among men and hypertension and stroke among women. Our results further demonstrate the centrality of the social and behavioral determinants of health by utilizing detailed information across the human genome and add to both social and genetic epidemiology literatures. Highlights: Obesity is known to be associated with poor cardiovascular health. Obesity is influenced by a combination of genetic and environmental factors. The genetic risks are polygenic, while environmental risks are social/behavioral. How one becomes obese matters for likelihood of later health problems. The "genetically" obese have better health than the "socially" obese in late life.